The transcriptional landscape of insect galls: psyllid (Hemiptera) gall formation in Hawaiian Metrosideros polymorpha (Myrtaceae). (December 2015) - Bailey, Sebastian; Percy, Diana; Hefer, Charles; Cronk, Quentin
Abstract Background Recent studies show that galling Hymenoptera and Diptera are able to synthesize the plant hormone indole-3-acetic acid (auxin) from tryptophan and that plant response to insect-produced auxin is implicated in gall formation. We examined the leaf transcriptome of galled and ungalled leaves of individuals of the Hawaiian endemic plantMetrosideros polymorpha (Myrtaceae) subject to infestation by psyllid (Hemiptera) gall-makers in the genusTrioza (Triozidae). Results Transcript libraries were sequenced using Illumina technology and the reads assembledde novo into contigs. Functional identification of contigs followed a two-step procedure, first identifying contigs by comparison to the completely sequenced genome of the relatedEucalyptus, followed by identifying the equivalentArabidopsis gene using a pre-computed mapping betweenEucalyptus andArabidopsis genes. This allowed us to use the rich functional annotation of theArabidopsis genome to assess the transcriptional landscape of galling inMetrosideros . Comparing galled and ungalled leaves, we find a highly significant enrichment of expressed genes with a gene ontology (GO) annotation to auxin response in the former. One gene consistently expressed in all galled trees examined but not detected in any libraries from ungalled leaves was theMetrosideros version of SMALL AUXIN UPREGULATED (SAUR) 67 which appears to be a marker for leaf-galling inMetrosideros . Conclusions We conclude that an auxin response is involved in galling byMetrosideros psyllids. The possibility should therefore be considered that psyllids (like other insects examined) are able to synthesize auxin.